(untitled) (Stato, Chiese e pluralismo confessionale, 2015)
Contributo sottoposto a valutazione SOMMARIO: 1. Simboli religiosi e competenze dell’Unione europea – 2. Il divieto di discriminazione del lavoratore e l’ammissibilità di regimi derogatori – 3. La problematica delimitazione della portata dell’art. 4, par. 1, della direttiva 2000/78/CE – 4. Il rinvio pregiudiziale davanti alla Corte di giustizia della questione del velo islamico – 5. (segue) I dubbi sull’eccessiva concretezza del quesito – 6. Gli orientamenti della giurisprudenza francese – 7. La libertà religiosa nell’impresa privata e le deroghe al diritto antidiscriminatorio: tre notazioni generali – 8. (segue) Il problema della rilevanza del requisito professionale “negativo” – 9. (segue) Gli spazi di operatività della discriminazione indiretta – 10. Divieto di discriminazione ed esigenze dell’impresa. Una conclusione provvisoria in attesa della pronunzia della Corte di giustizia. Abstract An employer refusing to hire an applicant (or discharging an employee) wearing an Islamic headscarf, because of the individual’s religious practice, could be seen as a case of discrimination based on religion and therefore contrary to Council Directive 78/2000/EC of 27 November 2000, establishing a general framework for equal treatment in employment and occupation. However, Article 4(1) of this Directive provides that a difference in treatment based on a characteristic related to the listed grounds of discrimination may not be discriminatory if a particular religion or belief is a genuine occupational requirements for the post. The article examines the question referred at the Court of Justice of the European Union from the Cour de cassation (France) on 24 April 2015: “Must Article 4(1) … be interpreted as meaning that the wish of a customer of an information technology consulting company no longer to have the information technology services of that company provided by an employee, a design engineer, wearing an Islamic headscarf, is a genuine and determining occupational requirement, by reason of the nature of the particular occupational activities concerned or of the context in which they are carried out?”